Al-Syahādah fī al-Islām wa al-Naṣāra (al-Jawāb ‘ala Mafhūm al-Najah fī alTa’addudiyah al-Dīniyah) - Harda Armayanto; Alia Syahida (Universitas Darussalam Gontor, 2017)
The safety discourse found in religious pluralism becomes a serious problem among the religions. Religious pluralism comes to offer a new concept in which salvation belongs to all religions. Everyone, whatever his religion, has the same chance to enter heaven. In fact, every religion has a unique concept of safety and special requirements to achieve it. The requirement in Islam is syahādat and in Christianity is the creed. In Islam, if you want to be saved, then you must embrace Islam by testifying that there is no god but Allah and testifying that Muhammad is His messenger. Whereas in Christianity, if he wants to be saved, he must be baptized by acknowledging his belief in the God of the Trinity, Maryam the mother of Jesus, and the Church. Thus, this paper attempts to reveal the concept of Syahādat in Islam and Christianity in response to the concept of salvation in religious pluralism. To find the similarities and differences between Syahādat and the creed. In this way it can be proved that the concept of salvation in religious pluralism which states salvation applies to all religions is wrong. Proven with the different conditions of salvation between Islam and Christianity. If the conditions are different, of course the results are also different.